Vitamin and zeatin treatments promote colchicine-induced haploid chromosome doubling in maize - Chen Chen; Yuling Zhang; Chenxu Liu; Jinlong Li; Jiuran Zhao; Yuandong Wang; Shaojiang Chen (Crop Journal)
Doubled haploid (DH) technology is an efficient method used in commercial maize breeding. Chromosome doubling is a vital step of DH technology; however, the underlying processes regulating chromosome doubling of haploid is still not well understood, which is key to optimize the technology. In this study, the immature haploid embryos of the maize inbred line Zheng58 treated with amiprophos-methyl (APM) or colchicine were used to analyze transcriptomic and metabolomic changes, 75 and 60 differential expressed metabolites (DEMs) were identified between control treatment, respectively. Most differentially expressed genes (DEGs) related to artificial chromosome doubling were down regulated; these were mainly involved in mitosis process. Both DEMs and DEGs co-expression analyses showed that, compared to controls, zeatin biosynthesis and cofactor and vitamin metabolism were significantly enriched in both APM and colchicine treatments. In a parallel experiment, exogenous vitamins including thiamine, nicotinic acid, vitamin B6, or trans-zeatin were added to colchicine treatment; there were synergistic effects between vitamins or zeatin and colchicine in haploid artificial chromosome doubling. These results provide novel insights in exploring the molecular responses to antimitotic reagents at both the transcriptomic and metabolomic levels. In addition, the application efficiency of haploid breeding will be greatly improved by the key factors for artificial chromosome doubling.